2018
DOI: 10.1002/arp.1730
|View full text |Cite
|
Sign up to set email alerts
|

Object‐based image analysis: a review of developments and future directions of automated feature detection in landscape archaeology

Abstract: Object-based image analysis (OBIA) is a method of assessing remote sensing data that uses morphometric and spectral parameters simultaneously to identify features in remote sensing imagery. Over the past 10-15 years, OBIA methods have been introduced to detect archaeological features. Improvements in accuracy have been attained by using a greater number of morphometric variables and multiple scales of analysis. This article highlights the developments that have occurred in the application of OBIA within archae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(98 citation statements)
references
References 63 publications
(115 reference statements)
0
97
0
1
Order By: Relevance
“…A main source of information comes from semi‐automatic detection of barrows, which is an up‐to‐date technique (Cerrillo‐Cuenca, ; Cowley, ; Davis, ; Guyot et al, ; Trier, Zortea, & Tonning, ). Our method is based on a GEOBIA (GEOgraphic‐Object‐Based Image Analysis) approach that segments the DTM raster into regions considering specific properties of the terrain.…”
Section: Methodsmentioning
confidence: 99%
“…A main source of information comes from semi‐automatic detection of barrows, which is an up‐to‐date technique (Cerrillo‐Cuenca, ; Cowley, ; Davis, ; Guyot et al, ; Trier, Zortea, & Tonning, ). Our method is based on a GEOBIA (GEOgraphic‐Object‐Based Image Analysis) approach that segments the DTM raster into regions considering specific properties of the terrain.…”
Section: Methodsmentioning
confidence: 99%
“…Nowadays, RS specialists and archaeologists are giving priority to manual visualization, which is limited to three spectral bands at a time [29]. This means that it is still necessary to intervene manually, which requires a lot of time, manpower and material resources [53][54][55]. With the rapid development of image and signal processing and computer vision, several (semi-) automatic approaches have also been designed for and applied to archaeological research [56][57][58][59][60].…”
Section: Archaeological Remote Sensingmentioning
confidence: 99%
“…Automatic feature detection approaches for archaeology are a rapidly and fast developing field in archaeological prospection [60][61][62]. Recent studies have demonstrated machine learning methods for detecting a wide variety of features, including burial mounds, charcoal kilns, buildings, and field systems [10,[63][64][65][66].…”
Section: Evaluating Our Approachmentioning
confidence: 99%